Intensity-modulated arc therapy to improve radiation dose delivery in the treatment of abdominal neuroblastoma. (March 2013) - Gains, Jennifer E; Stacey, Christopher; Rosenberg, Ivan; Mandeville, Henry C; Chang, Yen-Ch'ing; D'Souza, Derek; Moroz, Veronica; Wheatley, Keith; Gaze, Mark N
The standard European radiotherapy technique for children with neuroblastoma is a conventional parallel opposed pair. This frequently results in compromise on planning target volume coverage to stay within normal tissue tolerances. This study investigates the use of an intensity-modulated arc therapy (IMAT) technique to improve dose distribution and allow better protocol compliance. Among 20 previously treated patients, ten had received the full prescribed dose with conventional planning (protocol compliant) and ten had a compromise on planning target volume coverage (protocol noncompliant). All patients were replanned with IMAT. Dosimetric parameters of the conventional radiotherapy and IMAT were compared. The dose received by 98% of the planning target volume, homogeneity and conformity indices were all improved with IMAT (p < 0.001). IMAT would have enabled delivery of the full protocol dose in eight out of ten protocol-noncompliant patients. IMAT may improve outcomes through improved protocol compliance and better dose distributions.